Pelatihan Games Edukasi Digital bagi Guru IPA sebagai Upaya dalam Meningkatkan Motivasi Belajar Peserta Didik Di SMP Negeri 13 Makassar - Lisdayanti, Putri Diana; Saenab, Sitti; Faisal, Faisal; Saleh, Andi Rahmat; Hasan, Nurrajemi (JKM: Jurnal Kemitraan Masyarakat, 2025)
Digital educational games training aims to improve the competence of science teachers in understanding and implementing innovative learning media. The stages of the research include preparation, implementation and evaluation. Data were collected through a questionnaire of science teachers' responses in the digital educational games training. The results of the study showed tha the training which included the provision of material to hands-on practice was able to provide conceptual understanding as well as applicable skills to science teachers in designing digital game-based learning that was interactive and motivated students. After the training activities were carried out, the training participants gave a positive response, especially on the aspects of the attractiveness of the material and the completeness of the supporting facilities which each obtained the highest satisfaction score of 95%, but there were still aspects that needed improvement, namely the effective use of time and costs with the lowest score, namely 60%.